PENGARUH POLA ASUH ORANGTUA TERHADAP KEMAMPUAN GERAK DASAR SISWA (STUDI PADA SISWA KELAS XI SMAN 1 PROBOLINGGO) - NONI HAPSARI, ADINDA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Family is the first and the prime environment for children. In a family, children learn about norms, habits, responsibilities, and how to respect others. Children’s growth and development depends on how parents taking care and guiding their children in their home, certainly with the implementation of parenting method. By the right parenting methods, it would give positive impact towards children’s general motor ability. Those, is very important things that need to be concerned for supporting daily activities and making more dynamic life.This research is purposed for knowing the influence of parenting method toward the general motor ability in student on 11th grade in SMAN 1 Probolinggo. The type of this research is descriptive research with quantitative approach. Research design which is used for this research is correlational design. The population in this research is students of the eleven graders in SMAN 1 Probolinggo. Sampling by using cluster random sampling: sampling is not the individual but the group. The instrument that is used for knowing of parenting method is by using questionnaire whereas Barrow Motor Ability Test is used for knowing student’s general motor ability. Data analysis which is used is contingency coefficient.Based on the research, it can be concluded that among 35 students as a sample, 1 student got authoritative education, 6 students got permissive education, and 28 students got authority education. Results of the data calculation using SPPS 20.0 showed 0,584 result value and sig 0,021. It’s showed that sig (0,021) < alpha 0, 05 that is means Ho is rejected and H1 is accepted. In conclusion parenting method is influential towards the general motor ability in student on 11th Grade in SMAN 1 Probolinggo, that reaches 34,1%. Keywords: Parenting Method, General Motor Ability